The Structures of Fancy in Big Fish Directed by Tim Burton, Emphasizing the Opinions of Gilbert Durand - Hamed Momken; hasan bolkhari ghehi (هنرهای زیبا. هنرهای نمایشی و موسیقی)
The present study deals with the representation and analysis of structures from the film Big Fish directed by Tim Burton, using the opinions of Gilbert Durand. Durand was able to provide fancy, a faculty of imagination, in the Film’s reading of verbal and visual texts, using both Night and Day system. Also, repetitions and semantic redundancies are pointed out. Therefore, the fundamental problem would be the main functions of fancy in the Big Fish and how its artistic images can be classified based on Gilbert Durand's ideas. Accordingly, the aim of the present research is to identify the relationship between fancy (Edward Bloom) and truth (William Bloom) in the context of the events of the story using the two systems of Night and Day presented by Gilbert Durand. In this film, Burton tries to show the entire narrative as a kind of movement. A movement from the initial not knowing of Edward Bloom's son, to his final knowing. From the beginning of the narrative, the fictional system of the story's characters can be divided into two main subjects: fancy and truth. In fact, the images of the film are rotating around these two concepts. Here, two places, earthly and heavenly, can be seen. The earthly place refers to the city of Ashton and the heavenly place, to the city of Specter. The earthly place is opposed to the heavenly place, and Edward tries to move and travel from the earth to the sky with the help of the element of Fancy.In the Big Fish, Edvard Blum is hunting a huge animal that cannot be hunted by anyone and can only be hunted by a fisherman who himself is the catch. The fisherman (Edward) must bait himself, which is the wedding ring, to enter the structure of the Day and Night regimes. At the end of the film, with Edward's death, he turns into a large fish and begins a new life. In the final part of the film and in the final moments of Edward's life and before his death, he asks his son: How am I going? (not how I will die). The current research focuses on the subject with a fundamental approach and with a descriptive-analytical method, and the data is also collected based on library and electronic study. The findings of this research acknowledge that by benefiting from Gilbert Durand's comments, we can see that the director's fanciful view is influenced to some extent by the structures of the Night and Day system of fancy. The capability of fancy is an interval between death and resurrection.